Reproductive trajectories and social-biological dimensions in parenthood: Portuguese version of the Meaning of Parenthood scale - Henriques, A (2020)
Background: Public meanings attributed to parenthood may shape individuals’ family planning and how involuntary childlessness is supported by governmental policies. This study aimed to evaluate the influence of reproductive trajectories and gender in the meanings attributed to parenthood, and to assess the psychometric characteristics of the Portuguese version of the Meaning of Parenthood (MOP) scale. Methods: The sample comprised 754 participants: 246 young adults without children; 51 fathers and 159 mothers of adolescent children conceived spontaneously; and 149 infertile heterosexual couples. The scale was self-administered. Higher scores indicate attributing greater importance to parenthood to fulfill identity needs at individual, marital and social levels. Psychometric characteristics were analyzed through exploratory factor analysis; Cronbach alpha (α) assessed internal consistency. Results: Two dimensions of the MOP scale emerged, with good internal consistency (α ≥ 0.70): biological (importance of parenthood to fulfill reproductive needs as a biological being); social (importance of parenthood arising from social reproduction). Young adults attributed less importance to parenthood to fulfill both biological and social needs. The biological dimension was valued more than the social dimension in all subsamples; men highly valued the biological dimension compared to women. Conclusions: Family planning needs to focus on a reasonable balance between biological and social dimensions of parenthood. The reinforcement of public policies providing the necessary conditions for human reproduction is essential to reverse declining fertility rates.